Critique of the Teleological presuppositions of Peace-Conflict-Development Narrative Discourse in Africa - Solaja, Oludele; Adegoke, Damilola (Leadership and Developing Societies, 2023)
<p style="box-sizing: inherit; margin: 0px; padding: 0px; border: var(--artdeco-reset-base-border-zero); font-size: inherit; vertical-align: var(--artdeco-reset-base-vertical-align-baseline); background: var(--artdeco-reset-base-background-transparent); font-weight: var(--artdeco-reset-typography-font-weight-normal); --artdeco-reset-typography_getfontsize: 1.6rem; --artdeco-reset-typography_getlineheight: 1.5; line-height: var(--artdeco-reset-typography_getLineHeight); color: var(--color-text); cursor: text; counter-reset: list-1 0 list-2 0 list-3 0 list-4 0 list-5 0 list-6 0 list-7 0 list-8 0 list-9 0;">Implicit in the dominant conceptualisations of discursive peace about conflict and development is the intrinsic presupposition of peace as "the means" towards the cessation of conflict - "the end", whose by-product is necessarily development. Several works have interrogated and criticised this peace construct. These works often recast peace as a social fact imbued with a teleological implication towards progressive development ideals and the end of conflict. Western social philosophy, particularly Aristotelianism, heavily influenced this reductionist approach, as surmised in Book IV of his (Aristotle's) Political treatise. <p style="box-sizing: inherit; margin: 0px; padding: 0px; border: var(--artdeco-reset-base-border-zero); font-size: inherit; vertical-align: var(--artdeco-reset-base-vertical-align-baseline); background: var(--artdeco-reset-base-background-transparent); font-weight: var(--artdeco-reset-typography-font-weight-normal); --artdeco-reset-typography_getfontsize: 1.6rem; --artdeco-reset-typography_getlineheight: 1.5; line-height: var(--artdeco-reset-typography_getLineHeight); color: var(--color-text); cursor: text; counter-reset: list-1 0 list-2 0 list-3 0 list-4 0 list-5 0 list-6 0 list-7 0 list-8 0 list-9 0;">After examining several prominent works on peace, conflict, and development by scholars, we observe that their works are not immune from this utilitarian influence. Therefore, we argue for a refocusing and hermeneutical re-understanding of peace as a process in a continuum rather than the means towards an end. The paper, thus, critiques the teleological presuppositions of peace-conflict-development narrative discourse in classical and contemporary studies. Explanatory, historical designs and narratives using relevant examples from Africa and other communities in the global south were adopted to facilitate a better understanding of the subject.